TRANSFORMASI PEMILIH PEMULA: PERAN AKSES INFORMASI DAN KESADARAN HAK PILIH DALAM PEMILU - Muhammad Hilmi Masykur; Aziza Aziz Rahmaningsih; Hendra Irawan (JOURNAL IURIS SCIENTIA, 2026)
Historically, low turnout among first-time voters has often been driven by an information gap and inadequate outreach methods, coupled with the challenges of digital disruption that can create biased perceptions through viral content. This study aims to analyze the contribution of easy access to information through digital platforms and the level of voting rights awareness to the transformation of political participation patterns among first-time voters. Employing empirical legal research methods through a statute approach and a case study in Tulang Bawang Regency, data was collected through in-depth interviews and document studies. The results show a 28% surge in first-time voter participation in Tulang Bawang in the 2024 Election, driven by a shift in campaign patterns to digital spaces (such as TikTok and Instagram), which allow voters to independently analyze candidate programs. This finding marks a transformation in the participation model from merely passive mobilization to autonomous and substantive participation. In conclusion, the synergy between access to valid information and a strong awareness of voting rights has matured first-time voters into rational political actors who understand their moral and constitutional responsibilities, thereby directly improving the quality and substance of popular sovereignty in a democratic system.